Do deferred donors continue their donations? A large‐scale register study on whole blood donor return in the Netherlands - Spekman, Marloes L.C. (Transfusion, 2019)
BACKGROUND: Temporary deferral of whole blood donors is essential for a safe blood supply, yet deferral may impact donor return. Different deferral reasons may differently affect return, and donor experience may interfere with this. Therefore, we studied the joint effect of deferral reason and donor experience on return. STUDY DESIGN AND METHODS: We used a large‐scale retrospective cohort design including all Dutch donors with a whole blood donation attempt in 2013 to 2015 (n = 343,825). We established details of the target donation (including deferral reason if applicable), details of attendances in the 2 years after the target donation, donor characteristics (blood type, sex, age), and donor experience (first‐time, novice, experienced, reactivated). Descriptive statistics as well as time‐to‐events methods were used. RESULTS: Experienced donors were most likely to return, even after deferral (nondeferred 96% vs. deferred 92%). First‐time and reactivated donors were less likely to return after deferral (69 and 61%, respectively) compared to their nondeferred counterparts (82 and 76%, respectively). First‐time hemoglobin (Hb)‐deferred donors were less likely to return and slower to return than other donors. Similar results were found for reactivated donors deferred for short‐term medical reasons. CONCLUSION: Deferral reason and donor experience individually as well as jointly impacted donor return. Particularly first‐time and reactivated donors were at risk of nonreturn, especially when deferred for Hb or short‐term medical reasons, respectively. Blood banks designing and implementing donor retention strategies should thus not only take successful but also unsuccessful donation experiences and different experience levels into account.